2016
DOI: 10.1039/c5ta09179a
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient photoanodes based on cascade structural semiconductors of Cu2Se/CdSe/TiO2: a multifaceted approach to achieving microstructural and compositional control

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. Hydrogen produced by splitting water is receiving significant attention due to the rising global energy demand and growing climate concern. The photocatalytic decomposition of water conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Interestingly, Tan et al used Cu/CuS-ZnO/ZnS branched nanowires for PEC water splitting and observed that sonication provided higher photocurrent densities, which was due to a self-bias associated with the piezoelectric voltage created at the ZnO . A wide range of viable constructs is possible with, for example, Chong et al reporting the high performance of TiO 2 /CdSe/Cu 2 Se cascade architecture on a TiO 2 nanotube array structure (as photoanodes), where stable photocurrent densities of up to 20 mA cm −2 were demonstrated …”
Section: Catalytic Applicationsmentioning
confidence: 99%
“…Interestingly, Tan et al used Cu/CuS-ZnO/ZnS branched nanowires for PEC water splitting and observed that sonication provided higher photocurrent densities, which was due to a self-bias associated with the piezoelectric voltage created at the ZnO . A wide range of viable constructs is possible with, for example, Chong et al reporting the high performance of TiO 2 /CdSe/Cu 2 Se cascade architecture on a TiO 2 nanotube array structure (as photoanodes), where stable photocurrent densities of up to 20 mA cm −2 were demonstrated …”
Section: Catalytic Applicationsmentioning
confidence: 99%
“…Photoelectrochemical (PEC) water splitting under solar radiation is considered a promising strategy for producing hydrogen gas, which can serve as a highly energy-dense fuel with clean combustion byproducts . These systems rely on efficient and stable photoelectrodes, with the predominant focus in the field aimed at addressing low efficiency, limited long-term stability, and applicability restricted to the ultraviolet radiation region. Anodic metal oxides show promise for this purpose due to their unique geometry, , relatively high surface area, and properties such as light absorption ability and generation of charge carriers under illumination . Furthermore, photoelectrodes based on anodic oxides do not require elaborate preparation because of the relatively good adhesion between the porous film and a conductive metal, as well as its perpendicular orientation to the substrate, which facilitates an efficient electron transfer path .…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] Nevertheless, the photocorrosion problem is an inherent drawback of metal selenides. [ 7 ] It is, therefore, vital to inhibit photocorrosion via advanced surface engineering methods. The addition of carbon coating has been proved to be effective in inhibiting the photocorrosion.…”
Section: Introductionmentioning
confidence: 99%